Ordeals of Sexually Violated Women and Access to Comprehensive Healthcare: A Case Study of Victims of Sexual Violence in North Kivu, Eastern Congo - Mbuisi Eale Brigitte, Katshiete; Andersson, Gunnel; Namegabe Edmond, Ntabe; BwiraKaboru, Berthollet; Adolfsson, Annsofie (Journal of Women's Reproductive Health, 2018)
Background: The impact of sexual violence in any community is extremely devastating and women in the Eastern part of the Congo are no exception. Sexual violence not only affects the health of women, but it impacts their social life within the community too. Objective: The study aims to investigate the experiences of female victims of sexual violence in accessing medical care in North Kivu. Design: An interpretive, phenomenological approach was used for this inductive and qualitative study. In-depth informant interviews were the main data collection tool. Open-ended questions were used during the interviews in order to garner more information from the interviewees. Heidegger’s approach was utilized in analyzing the collected data. Results: The analyzed and interpreted results of the data indicated that survivors of sexual violence are engaged in an ongoing struggle. The victims demonstrated immense resilience despite the lack of comprehensive medical care and have continued to reassemble their broken lives. In order to present the outcomes of the research in a succinct and coherent manner, the outcomes are categorized into five sub-themes: managing worries and shame; regaining happiness; healing and restoration; the need for professional assistance and struggles in daily life. Conclusion: The study provides an understanding of the recovery processes of survivors of sexual violence in North Kivu, with important insights into dimensions that rehabilitation programs should take into consideration.
Keywords: Eastern Congo; healthcare; North Kivu; ordeals; sexual violence; victim; women.